2009
DOI: 10.1182/blood.v114.22.2018.2018
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Molecules and Inflammatory Cytokines in Patients with Thalassemia Major and Double Heterozygous HbS/Beta-Thalassemia; the impact of Deferasirox.

Abstract: 2018 Poster Board I-1040 Angiogenesis is a crucial process in the pathogenesis of several inflammatory, autoimmune and malignant diseases. Endothelial damage and inflammation make a significant contribution to the pathophysiology of sickle cell disease (SCD) and the beta-thalassemia syndromes. However, there are very limited data in the literature for the role of angiogenic cytokines in the pathogenesis of thalassemia major (TM) and of double heterozygocity of SCD and beta-thalass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this regard, Voskaridou et al 29 reported that patients with β-TM had increased levels of angiogenic cytokines such as VEGF, basic fibroblast growth factor, angiogenin, and angiopoietin compared to healthy controls. Also, Butthep et al 30 reported that patients with thalassemia are characterized by increased levels of VEGF and tumor necrosis factor (TNF).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Voskaridou et al 29 reported that patients with β-TM had increased levels of angiogenic cytokines such as VEGF, basic fibroblast growth factor, angiogenin, and angiopoietin compared to healthy controls. Also, Butthep et al 30 reported that patients with thalassemia are characterized by increased levels of VEGF and tumor necrosis factor (TNF).…”
Section: Discussionmentioning
confidence: 99%